2010
DOI: 10.1016/j.neuroscience.2009.11.015
|View full text |Cite
|
Sign up to set email alerts
|

AMPA receptor subunit GluR1 downstream of D-1 dopamine receptor stimulation in nucleus accumbens shell mediates increased drug reward magnitude in food-restricted rats

Abstract: Previous findings suggest that neuroadaptations downstream of D-1 dopamine (DA) receptor stimulation in nucleus accumbens (NAc) are involved in the enhancement of drug reward by chronic food restriction (FR). Given the high co-expression of D-1 and GluR1 AMPA receptors in NAc, and the regulation of GluR1 channel conductance and trafficking by D-1-linked intracellular signaling cascades, the present study examined effects of the D-1 agonist, SKF-82958, on NAc GluR1 phosphorylation, intracranial electrical self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 71 publications
3
64
1
Order By: Relevance
“…Moreover, stimulation of dopamine D 1 receptors in the Nacc shell phosphorylates AMPA receptors, thereby strengthening the function of AMPA receptors (40). Therefore, an alternative explanation concerning the above-mentioned results is that NMDA and AMPA receptors postsynaptically modulate the dopamine function, possibly via D 1 receptors.…”
Section: Glutamatementioning
confidence: 96%
“…Moreover, stimulation of dopamine D 1 receptors in the Nacc shell phosphorylates AMPA receptors, thereby strengthening the function of AMPA receptors (40). Therefore, an alternative explanation concerning the above-mentioned results is that NMDA and AMPA receptors postsynaptically modulate the dopamine function, possibly via D 1 receptors.…”
Section: Glutamatementioning
confidence: 96%
“…Moreover, we have recently reported that blockade of DA D1-, but not D2-like receptors, attenuated acute food deprivation-induced reinstatement of heroin seeking (Tobin et al, 2013). In addition, chronic food restriction increases synaptic plasticity in NAc cells expressing DA D1-like, but not D2-like, receptors (Carr et al, 2003(Carr et al, , 2010. Consequently, here we administered a DA D1-like receptor antagonist into the NAc shell and core to determine if DA transmission via the D1-like receptors is causally related to the augmentation of heroin-seeking induced by chronic food restriction.…”
Section: Introductionmentioning
confidence: 94%
“…Activation of dopamine D1 receptors (D1Rs) has been shown to increase GluA1 Ser-845 phosphorylation and induce membrane insertion in striatal neurons through a PKA-dependent mechanism (37)(38)(39)(40). Nitric oxide signaling plays a prevalent role in modulating MSN excitability (41), and cGMP plays an important role in this regulation (42,43), but the mechanisms by which it regulates MSN synapses are unknown.…”
mentioning
confidence: 99%